Mechanisms of hydrogen embrittlement in steels: discussion. (28th July 2017) - Dear, Felicity F.; Skinner, Guy C. G.
Abstract : This discussion session interrogated the current understanding of hydrogen embrittlement mechanisms in steels. This article is part of the themed issue 'The challenges of hydrogen and metals'.